Sinonasal and Skull Base Morbidity from a Modified Nasoseptal Flap versus No Flap in Pituitary Surgery - Khoo, Ash Li; Seresirikachorn, Kachorn; Oakley, Gretchen M.; Barham, Henry P.; Grayson, Jessica W.; Orgain, Carolyn; Alvarado, Raquel; Mangussi-Gomes, João; Kalish, Larry H.; Campbell, Raewyn G.; Harvey, Richard J. (Journal of Neurological Surgery Part B: Skull Base, 2025)
Durable sellar reconstruction and preserving sinonasal function are pivotal objectives in endoscopic pituitary surgery.This study aimed to investigate the postoperative skull base and sinonasal morbidity associated with a modified nasoseptal flap (NSF) in endoscopic pituitary surgery.A retrospective cohort study was conducted on patients undergoing endoscopic transsphenoidal pituitary surgery with either an NSF or non-NSF reconstruction of the sella. Patients had an obvious or suspected intraoperative cerebrospinal leak. A minimum 6-month follow-up was required. Outcome measures included postoperative skull base morbidity (cerebrospinal fluid leak, flap necrosis, pneumocephalus, meningitis, other intracranial infections, intracranial hemorrhage), sinonasal morbidity (epistaxis, crusting, sinus infection, atrophic rhinitis, persistent crusting, sinus dysfunction, mucocele formation, septal perforation), and patient-reported outcome measures (Sinonasal Outcome Test 22 [SNOT22; range 0–110], Nasal Symptom Score [NSS; range 0–30], and olfactory dysfunction score [range 0–5]).About 372 patients (age 53.8 ± 16.7 years, 53.5% female) were included. Most patients underwent NSF reconstruction (87.1%). There was no significant difference in skull base morbidity between the NSF and non-pedicle flap groups. The NSF group had fewer self-reported sinus infections (0.9% vs. 6.4%, p = 0.03) and sinus dysfunction (2.8% vs. 31.3%, p < 0.01). Postoperative SNOT22 (12.9 ± 15.3 vs. 25.2 ± 21.3, p < 0.01), NSSs (2.3 ± 3.5 vs. 5.9 ± 6.0, p < 0.01), and olfactory dysfunction score (percentage of cases ≥“moderate problem [score 3],” 6.4% vs. 26.3%, p = 0.01) were also lower in the NSF group.Utilizing a modified NSF in endoscopic transsphenoidal pituitary surgery allows for a sellar reconstruction option without detrimental impact on sinonasal function.
Keywords: morbidity; nasoseptal flap; pituitary surgery; sinonasal; skull base